How fintech companies' capital structure influences their financial performance - Khusna, Lana Milatul; Rahadian, Dadan (Edelweiss Applied Science and Technology, 2025)
This research examines the impact of leverage, the Debt to Equity Ratio (DER), long-term debt, and short-term debt on the Return on Assets (ROA) of financial technology (FinTech) companies. A quantitative approach with a descriptive method was employed, involving 12 FinTech companies selected through purposive sampling, observed from Q1 2020 to Q4 2023. The analysis was carried out using multiple linear regression, classical assumption tests, and hypothesis tests. The results of the study show that leverage and DER have a positive effect on ROA, which means that the use of debt can increase profitability if managed properly. Conversely, long-term debt has a negative effect on ROA, indicating that long-term debt burdens can reduce profitability due to high interest costs. Meanwhile, short-term debt has no effect on ROA, indicating that short-term debt is used more for operational needs without a significant impact on profitability. The conclusion highlights the importance of optimizing leverage and DER to enhance profitability while cautioning against excessive long-term debt. Practical implications include providing insights for FinTech management to optimize capital structure, aiding investors in making informed decisions, and guiding regulators in promoting healthy financial practices within the industry.